2020
DOI: 10.1111/ijlh.13244
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of ADAMTS13 and von Willebrand factor in thromboembolic events in patients infected with SARS‐CoV‐2

Abstract: Since early in 2020, the first people in Europe were infected with the SARS-CoV-2 virus leading to the COVID-2019 pandemic. In March 2020, we admitted the first patients with a SARS-CoV-2 infection in our hospital. Many of these patients eventually end upThis is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
81
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(92 citation statements)
references
References 13 publications
6
81
0
5
Order By: Relevance
“…In COVID-19, signs of localized pulmonary TMA were observed with typical microvascular platelet-rich thrombi identified in small vessels of the lungs and other organs. Von Willebrand factor antigen and activity were reported to be elevated and ADAMTS13 levels to be decreased, although remaining higher than 10% [27,36,37]. However, schistocytes were not identified on blood smears, signs of hemolysis were absent and platelet count was higher than expected in this condition [27].…”
Section: Introductionmentioning
confidence: 65%
See 1 more Smart Citation
“…In COVID-19, signs of localized pulmonary TMA were observed with typical microvascular platelet-rich thrombi identified in small vessels of the lungs and other organs. Von Willebrand factor antigen and activity were reported to be elevated and ADAMTS13 levels to be decreased, although remaining higher than 10% [27,36,37]. However, schistocytes were not identified on blood smears, signs of hemolysis were absent and platelet count was higher than expected in this condition [27].…”
Section: Introductionmentioning
confidence: 65%
“…Previous studies identified possible direct infection of endothelial cells by SARS-CoV-2 with endothelialitis [34] and increased circulatory endothelial cells, an indicator of endothelial damage [35]. As in many severe inflammatory states, thrombotic microangiopathy (TMA) may develop secondary to acquired deficiency of ADAMTS13 and subsequent increase in large von Willebrand factor multimers [27,36]. In COVID-19, signs of localized pulmonary TMA were observed with typical microvascular platelet-rich thrombi identified in small vessels of the lungs and other organs.…”
Section: Introductionmentioning
confidence: 99%
“…2). The increase in VWF suggests a possible similarity to thrombotic thrombocytopenic purpura, however, ADAMTS13 (a disintegrin and metalloproteinase with a thrombospondin type 1 motif, member 13) levels in COVID-19 although reported to be decreased, may not be severely depleted as in thrombotic thrombocytopenic purpura [26]. The increased VWF levels to 3-4 times normal values seen in patients with COVID-19 may overwhelm the ADAMTS13 activity to degrade the ultra large VWF multimers.…”
Section: The Endothelial Damage-derived Hypercoagulabilitymentioning
confidence: 96%
“…Although there have been some COVID-19 data involving ADAMTS13 levels, the small sample size in these reports precluded any major conclusions. [11][12][13] variables, two-sample Student t tests, and one-way ANOVA for three group comparisons. Youden's J statistics was used to find the optimal cutpoint for ADAMTS13 for mortality.…”
Section: Introductionmentioning
confidence: 99%